1994
DOI: 10.7863/jum.1994.13.9.701
|View full text |Cite
|
Sign up to set email alerts
|

Gastroschisis: can sonography of the fetal bowel accurately predict postnatal outcome?

Abstract: To determine whether prenatal sonographic features of the small bowel can accurately predict postnatal outcome in fetuses with gastroschisis, the sonograms of 24 fetuses with prenatally detected gastroschisis were retrospectively reviewed for fetal bowel features including small bowel dilatation and bowel wall thickening. To identify a relationship between the sonographic features and neonatal outcome, each feature was analyzed against eight adverse clinical outcome measures including bowel obstruction or atre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 9 publications
6
51
1
10
Order By: Relevance
“…Methods such as umbilical artery Doppler velocimetry, cardiotocography and biophysical profile, are considered to be unaffected by an abdominal wall defect and may be helpful in determining if uteroplacental insufficiency is present. Some will also measure the bowel diameter, since it has been shown that a diameter of > 1 cm is a marker of prenatal bowel damage 11,12 . However, it is important to note that this reflects the fact that gastroschisis is often associated with other gut anomalies (e.g.…”
Section: Pregnancy Surveillancementioning
confidence: 99%
“…Methods such as umbilical artery Doppler velocimetry, cardiotocography and biophysical profile, are considered to be unaffected by an abdominal wall defect and may be helpful in determining if uteroplacental insufficiency is present. Some will also measure the bowel diameter, since it has been shown that a diameter of > 1 cm is a marker of prenatal bowel damage 11,12 . However, it is important to note that this reflects the fact that gastroschisis is often associated with other gut anomalies (e.g.…”
Section: Pregnancy Surveillancementioning
confidence: 99%
“…These studies have tended to be small and limited to the cases treated by one unit. Neonatal survival following the antenatal detection of gastroschisis has been reported to be as high as 92% to 94% (Babcook et al 1994), (Brun et al 1996). Follow-up studies have been carried out over a variety of time periods.…”
Section: Post-natal Management and Outcomementioning
confidence: 99%
“…One reason for early intervention and delivery would be if bowel dilatation or wall thickening noted on antenatal ultrasound scan predicted the outcome for gastroschisis cases (Langer et al 1993). However, such findings have been shown to be poor predictors of post-natal bowel complications (Babcook et al 1994) and as preterm delivery has its own associated risks it is recommended only if there is convincing evidence that it will improve the outcome for gastroschisis cases. Burge et al (1997) suggest that gastroschisis cases are at significant risk of fetal distress that could indicate either an increased risk of intra uterine death or adverse neurological outcome.…”
Section: Delivery and Perinatal Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Le taux de survie est passé de 20% en 1960 à 85-90% actuellement [38]. Dans notre série, parmi les 22 enfants opérés, trois sont décédés dans les trois premiers mois.…”
Section: éVolution Postnatale Et Devenir Sans Morbiditéunclassified